Late Tertiary reorganizations of deformation in northeastern Tibet constrained by stratigraphy and provenance data from eastern Longzhong Basin. Issue 8 (10th August 2015) - Liu, Shanpin; Li, Jijun; Stockli, Daniel F.; Song, Chunhui; Nie, Junsheng; Peng, Tingjiang; Wang, Xiuxi; He, Kuang; Hui, Zhengchuang; Zhang, Jun
Abstract The deformation of the Tibetan Plateau is central to unraveling the process and mechanism of continental tectonics. Although most agree that crust shortening and plateau growth were protracted throughout the Cenozoic Indo‐Asian collision, particular deformation histories relating to tectonic kinematics and dynamics are still incomplete due to sparseness of diagnostic geological information from plateau margin. Here we present combined investigation of stratigraphy, magnetostratigraphy, and provenance for the eastern margin of Longzhong Basin to show two reorganizations of basin formation and tectonic regime during the late Tertiary. First, the depocenter migrated from the dispersed Paleogene sequences to the Wushan‐Tianshui foreland sequence during the earliest Miocene (circa 22 Ma), accompanied by shift of sedimentary provenance from double sources including the eastern Qilian block and eastern West Qinling terrain to single source within the West Qinling. It suggests reorganization of deformation from NW‐SE extension to NE‐SW contraction and initial uplift of the eastern West Qinling. Second, massive coarse‐grained fluvial beds were revived in the Wushan Basin during the late Miocene (circa 10 Ma), associated by eastward depositional expansion and another shift of sedimentary provenance toward northeast. It reflects thrusting up of the northern edge of the West Qinling and Liupan Shan Mountains linked with relocation of crust shortening from NE‐SW direction to ENE‐WSW direction and accelerated deformation of northeastern Tibet. These transitions of deformation regimes imply variation of geodynamic mechanisms during the process of plateau growth.